A model for examining the role of the Internet of Things in the development of e-business. Issue 1 (22nd October 2019) - Esmaeilpour Ghouchani, Babak; Jodaki, Susan; Joudaki, Maryam; Balali, Alireza; Rajabion, Lila
Abstract : Purpose: Nowadays, the Internet of Things (IoT) offers new intelligent services and business model opportunities by extending the internet connectivity into physical devices and daily objects. Recently, this technology has had a deep impact on all the aspects of human societies from industry to management and business. Therefore, the purpose of this paper is to predict the impact of using IoT services on the development of electronic business (e-business). Design/methodology/approach: For evaluating the model's elements, a questionnaire was designed. It was revised by experts with significant experiences. For statistical analysis, SmartPLS 3.2 is used. Findings: The findings have confirmed the validity of the proposed model. The results also have indicated that the quality of IoT services (scalability, availability, reliability and ease of use), security of IoT services (trust, reputation, privacy and encryption) and IT knowledge of users (usage skills, awareness, experience and accuracy) have a positive and significant impact on development of e-business. Furthermore, the obtained results have revealed that the operating cost of IoT services (transmission time, storage capacity, functionality and stability) is significantly influenced by the development of e-business. Research limitations/implications: By capturing a number of important factors in the proposed model, this study can provide a significant theoretical influence for researchers in the related area of interest. In fact, this study provides a worthwhile direction by assessing e-business performance, which, so far, has not been well assessed in many developing countries. Practical implications: From a practical perspective, the statistical results support the crucial role of the following factors: quality of IoT services, the security of IoT services, operating cost of IoT services and IT knowledge of users. Hence, aspects relating to these factors must be the focus of attention of any organization in their endeavor to development of e-business. Originality/value: This study meaningfully contributes to the knowledge and literature by focusing more on development e-business and IoT as original technology for further understanding, investigating other important features and applying advanced statistical analyses technique. By doing so, this study was able to develop the current understanding regarding the main aspects of development e-business and IoT services.